PSYCHO-SOCIAL CONGRUENCES BETWEEN RESILIENCE AND SOLITUDE - HARAZ Svetlana; SIMION Simion Dănuț (EcoSoEn: Ştiinţe Economice, Sociale şi Inginereşti = Economics, Social and Engineering Sciences)
People always interact and accumulate experience. The experience makes us stronger, more resilient by knowing our resources, developing constructive behaviors for potentially traumatic situations. The ability to face unfortunate events (losses, traumas, crises, disability, continuous stress, etc.) is the resilience that we all possess, that state to recover and move on, to face challenges and overcome difficulties in a positive and resilient way. How we develop our individual psychological resilience is determined by a multitude of factors: our ability to adapt to change, accept change and continue to interact positively socially, by the individual tools we use in adverse situations, by social support network, contextual social factors, etc. Resilience and loneliness can be interconnected in several ways. While resilience refers to an individual's ability to bounce back or recover from adversity, solitude refers to the assumed and conscious state of being alone with oneself in a willful, not accidental, way. Solitude provides individuals with a space to engage in cognitive processing and problem solving. When alone, people can focus their attention on complex problems or stressful situations, allowing them to analyze the situation, generate potential solutions, and make decisions without external distractions. This cognitive processing and problem-solving capacity can enhance resilience by helping individuals develop effective strategies to overcome challenges. Solitude can serve as a means of rest and recovery, which are essential components of resilience. Taking time for oneself, away from the demands of others, allows individuals to recharge their mental and emotional resources. This recharging of energy and restoration of well-being through solitude can contribute to an individual's ability to recover from stressors and setbacks. It is important to note that while solitude can be beneficial for resilience, excessive or prolonged isolation can have negative effects on mental health. It is essential to find a balance and ensure that individuals have access to social support networks, as human connection that also plays a significant role in building resilience.